The robustness and efficiency of monetary policy rules as guidelines for interest rate setting by the European Central Bank: Conference on Monetary Policy Rules, Stockholm 12 - 12 June 1998 - John B. Taylor (Sveriges Riksbank, 1998)
This paper examines the implications of recent research on monetary policy rules for practical monetary policy making, with special emphasis on strategies for setting interest rates by the new European Central Bank (ECB). The paper draws on recent research and new simulations of a large open economy model to assess the efficiency of a simple benchmark rule in comparison with other proposed rules. The paper stresses new results on the robustness of monetary policy rules in which each rule that is optimal or good according to one model or researcher is tested for robustness by other researchers using different models. Because of the large increase in the number of economists focussing on econometric evaluation of monetary policy rules for the interest rate instrument and because of the parallel increase in the variety of models being developed for this purpose, much more evidence is becoming available on the robustness of simple monetary policy rules for the interest rate than ever before.
Keywords: 330